Pseudosocka Beds with Coal in Borehole Tdp-1/84 Trobni Dol (Eastern Sava Folds, Slovenia) - Grad, Karel; Dozet, Stevo; Petrica, Rajko; Rijavec, Lija (Geologija, 1996)
The sedimentary succession with coal in the Trobni Dol area was studied in detail. The coal district lies east of Laško and belongs to the eastern part of the Sava folds. Every attention was given to the stratigraphic problems of the Egerian succession as well as to the coal, his stratigraphic position and age. The Pseudosocka beds are subdivided into the lower Pseudosocka beds, the coal horizon and the upper Pseudosocka beds. The coal seams of the Trobni Dol sedimentary succession were formed in the Upper Oligocene, the Lower Egerian respectively. Finally, the correlation of the Pseudosocka beds from Trobni Dol and western Laško synclinorium area was performed.